Efectos de la regulación hormonal sobre la dinámica mitocondrial y su impacto sobre la localización subcelular de proteínas claves en el transporte de colesterol en células esteroidogénicas - Fiore, Ana Zulma (2019)
Although there are numerous studies on the participation of mitochondrial\ndynamics (a balance in fusion/fission events and changes in the subcellular distribution\nof mitochondria) in many key cellular processes, as well as in various human pathologies,\na possible role of the mitochondria dynamics in the efficient production of steroids has\nbeen little explored. Mitochondria are central organelles during the synthesis of steroids,\nsince the first common step in this synthesis is the transport of cholesterol from the\ncytoplasm to the internal mitochondrial membrane, a step that limits steroidogenesis.\nThis step is regulated by multiple mechanisms, such as the induction of an enzyme, Acyl-\nCoA synthetase type 4 (Acsl4), its location in membranes of endoplasmic reticulum\nlinked to mitochondria (MAM) and the presence of the Steroidogenic Acute Regulatory\nprotein (StAR) and occurs in an acute stage and a chronic one. In the mitochondria and\nthe endoplasmic reticulum are multiple enzymes necessary to produce the final steroid\nhormone, so the study of mitochondrial dynamics in steroid-producing cells is of great\ninterest. In our laboratory, we have started a few years ago in the study of mitochondrial\ndynamics in steroid-producing tissues. We have described that PKA-dependent\nhormonal stimulation promotes the fusion of mitochondria in a time-dependent manner,\nin the line of murine Leydig cells, MA-10. In this thesis work, we continued with our\nprevious studies and showed that hormonal stimulation with the trophic hormone\nchorionic gonadotrophin (hCG) or an analog of the second messenger of the hormone,\n8Br-cAMP, positively regulates the mitochondrial levels of Mitofusin 2 (Mfn2), a key\nprotein in the fusion of mitochondria. This modulation is maintained until 24 h of\nstimulation, being important in the chronic stage of the hormonal regulation of\nsteroidogenesis. This increase depends on the expression of a phosphatase, SHP2,\nwhich we have already described as a key enzyme in mitochondrial fusion. We also\ndemonstrate in this work the hormonal modulation of OPA-1, a protein that participates\nin the fusion of mitochondrial crests. In line with these results, we detected that the\nDynamin-related protein (Drp1), the protein involved in fission, increases its levels in\nmitochondria with hormonal stimulation, observing that this protein is phosphorylated in\nmitochondria of MA-10 cells, which can decrease its pro-fission activity. This leads to a\nnet balance towards mitochondrial fusion. Hormonal stimulation promotes the mitochondrial localization of different enzymes, as we have already described, and in\nparticular, in this work we have observed that the presence of Mfn2 is necessary for the\nexpression and localization of Acsl4, whereas the mitochondrial localization of PKA does\nnot depend on Mfn2. It is concluded that the fusion could therefore be a mechanism for\nsome proteins to associate correctly with the mitochondria. These discoveries highlight\nthe importance of the reorganization of organelles in specialized cells, which drives the\nexploration of the impact that this dynamic has on biological processes that include,\namong others, the synthesis of steroids.